Development and eruption of human teeth in the Chinese population: a comprehensive dental atlas - Jayaraman, Jayakumar (Frontiers in Dental Medicine, 2024)
Aim The first comprehensive chart on dental development was published 75 years ago based on Caucasian children and this has been used as a standard dental chart to date. Few population specific charts have been developed recently and updated dental charts on modern subjects can provide more information on dental development patterns. This study aims to construct a comprehensive dental atlas for modern Chinese children and young adults to assist in clinical, forensic, and public health applications. Methods The study sample comprised of 2,306 subjects, age ranging from 2 to 24 years belonging to Chinese ethnicity. Dental formation and eruption of permanent teeth and resorption of primary teeth were analyzed separately for females and males. For each age range, the number of teeth (n), and the stage of development was calculated for first (Q1), second (Q2) and third quartiles (Q3). Similar analysis was performed for the position of permanent teeth and the resorption of primary teeth. To determine the variations between the sex, Mann-Whitney U-test was conducted by comparing the median (Q2) stages. Results Variations in dental formation and eruption of permanent teeth and resorption of primary teeth were observed between maxillary and mandibular dentitions and between the sex, however the difference was not statistically significant (p = 0.535 to p = 1.000). The dental atlas was presented separately for Chinese females and males. Conclusion This atlas on modern Chinese population serves as a practical tool to assist in clinical diagnosis and treatment planning, in forensic investigations as well as indicators of developments in public health.